International practice of corticosteroid replacement therapy in congenital adrenal hyperplasia: data from the I-CAH registry - (:unkn) unknown (BIOSCIENTIFICA LTD, 2021)
Objective: Despite published guidelines no unified approach to hormone replacement in congenital adrenal hyperplasia (CAH) exists. We aimed to explore geographical and temporal variations in the treatment with glucocorticoids and mineralocorticoids in CAH. Design: This retrospective multi-center study, including 31 centers (16 countries), analyzed data from the International CAH Registry. Methods: Data were collected from 461 patients aged 0-18 years with classic 21-hydroxylase deficiency (54.9% females) under follow-up between 1982 and 2018. Type, dose and timing of glucocorticoid and mineralocorticoid replacement were analyzed from 4174 patient visits. Results: The most frequently used glucocorticoid was hydrocortisone (87.6%). Overall, there were significant differences between age groups with regards to daily hydrocortisone-equivalent dose for body surface, with the lowest dose (median with interquartile range) of 12.0 (10.0-14.5) mg/m(2)/day at age 1-8 years and the highest dose of 14.0 (11.6-17.4) mg/m(2)/day at age 12-18 years. Glucocorticoid doses decreased after 2010 in patients 0-8 years (P < 0.001) and remained unchanged in patients aged 8-18 years. Fludrocortisone was used in 92% of patients, with relative doses decreasing with age. A wide variation was observed among countries with regards to all aspects of steroid hormone replacement. Conclusions: Data from the I-CAH Registry suggests international variations in hormone replacement therapy, with a tendency to treatment with high doses in children.